Activated carbon monoliths from lignocellulosic biomass waste for electrochemical - Rosas-Martínez, Juana María; Ibeh, Paul O.; García-Mateos, Francisco José; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2019)
The valorization of lignocellulosic biomass waste into bio-based materials is proposed in this work in order to obtain low-cost materials and to reduce environmental impacts. Cylindrical activated carbon monoliths (ACMs) were prepared from Alcell®, Kraft lignin and olive stone by chemical activation with H3PO4. To our best knowledge, there is no previous information about the preparation of ACMs from any type of lignin. The extrusion of the adequate mixing, without any kind of binder, was carried out in an extruder designed by ourselves with different dies. Carbon monoliths without and with holes (25 or 120 channels/cm2) were obtained. In case of lignin precursors, a stabilization step was optimized to minimize the problems of plasticity and swelling of lignin. N2 adsorption-desorption at -196 ºC and Hg porosimetry results show that activated carbon monoliths presented pore size distributions in the micro and mesopore range, with high surfaces areas (c.a. 1500 m2/g) and relatively high mesopore volume (0.35 cm3/g). The bulk density of the monoliths is also very high (~1.1 g/cm3 for ACM from Alcell lignin), with compressive strength of 7.6 MPa. Electrochemical characterization of binderless activated carbon monolith electrodes was carried out by cyclic voltammetry and galvanostatic charge-discharge techniques. The ACM from olive stones presents the highest specific capacitance, with approximately 217 F/g and 205 F/cm3.
Keywords: Química; Activated carbon monoliths; Lignocellulosic biomass; ACMs; Ingeniería química; Carbono